Analysis Of Community Satisfaction Index (SMI) Survey On One Door Integrated Services (PTSP) - Fina Nurmita (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2022)
This study aims to assess the index of community satisfaction with one-stop integrated services (PTSP) at the Regional Office of the Ministry of Religion of Bengkulu Province. The unit of analysis is the community that uses services such as legalizing marriage books, legalizing diplomas and others. The results of the descriptive analysis show that the Community Satisfaction Index (IKM) of service users such as legalizing marriage books, legalizing diplomas and others is 3.56 with very good criteria. The results of the analysis of each IKM parameter can be seen as follows; (1). Requirements is Good with a score of 3.48; (2) Systems, mechanisms and procedures is Good with a score of 3.47; (3) Completion Time is Good with a score of 3.35; (4) Cost/Tariff is Very Good with a score of 3.98; (5) Product specification type of service is Good with a score of 3.38; (6) Excellent implementing competence is very good with a score of 3.53; (7) The behavior of the implementer is very good with a score of 3.54; (8) Handling complaints, suggestions and inputs is Good with a score of 3.44; (9) Facilities and Infrastructure is Very Good with a score of 3.82. Thus, the index value is 3.56, then the IKM value after conversion (Index Value x Basic Value), namely; 3.56 x 25 = 88.9.